The national imagination of American Jews: from the liberal and Zionist cultural pluralism of Horace Kallen to the uncertainties of the 21st century (Tempo e Argumento, 2021)
In the early 20th century debate about the incorporation of European immigrants, two perspectives shared the view that the American nation was based on civic values, but differed on the forms of incorporation: on the one hand, Israel Zangwill’s melting-pot; on the other, Horace Kallen’s cultural pluralism. When developing his idea, Kallen proposed, in addition, that the Jews of the United States should construct their American identity articulating Zionism and liberalism. After World War II, Jews in the United States would, therefore, have built a national imagination based on these two cultural and political axes. Since the 1970s, however, the Zionist consensus of American Jews has eroded, which, along with demographic chances, brings new challenges to their national imagination at the beginning of the 21st century.